Perbandingan Pengaturan Tata Hukum Antara Indonesia dan Amerika Serikat - Siregar, Barly Harly; Fadhil, Rahmad; Kutub, Sayyid; Sarah, Aulia; Hasibuan, Mutiah Aminarti; Syahputri, Tri; Dewi, Delima Puspita; Harahap, Muthia Sartika; Rahma, Hidayatul; Siregar, Risnawati; Andini, Tatya Zahra; Siregar, Haiqal Rahman (Ikatan Da'i Indonesia, 2024)
Perhaps the most important development in patients' rights has been that in Indonesia and the United States regarding the doctrine of informed consent. Embracing the Continental European legal system, the doctrine of informed consent in Indonesia is articulated in Law No. 36 of 2009 on Health, Government Regulation No.32 of 1996 on Health Worker, Law No.29 of 2004 on Medical Practice, and Law No. 8 of 1999 on Consumer Protection. It is also specifically regulated by Health Ministerial Decree No. 29 of 2008 regarding Medical Action Approval. This doctrine requires physicians to share certain information with patients before asking for their consent to treatment. The Court in the United States of America used the term of informed consent to describe the physicians obligations to provide information. The legal consequences if informed consent is not given, it is considered as an act of abuse (intentionally) to the patient. According to Rule of law in the United States that physicians have to open all the information about all the necessary facts, so that patients can determine appropriate treatment options. Tort Law in Anglo-Saxon legal system, similar to